2014
DOI: 10.1161/jaha.114.000902
|View full text |Cite
|
Sign up to set email alerts
|

HDL‐3 is a Superior Predictor of Carotid Artery Disease in a Case‐Control Cohort of 1725 Participants

Abstract: BackgroundRecent data suggest that high‐density lipoprotein cholesterol (HDL‐C) levels are likely not in the causative pathway of atheroprotection, shifting focus from HDL‐C to its subfractions and associated proteins. This study's goal was to determine which HDL phenotype was the better predictor of carotid artery disease (CAAD).Methods and ResultsHDL‐2 and HDL‐3 were measured in 1725 participants of European ancestry in a prevalent case‐control cohort study of CAAD. Stratified analyses were conducted for men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
(69 reference statements)
1
31
0
2
Order By: Relevance
“…Functional aspects of the HDL-P not captured by HDL-C measures may explain the recent failures of interventions to raise HDL-C to prevent CVD mortality ( 8,15 ). Of the many functional aspects of HDL, one of the most promising is RCT, whereby lipids are removed from peripheral cells and atherosclerotic plaque by HDL-borne association between PLTPa and acute CVD ( 37,62 ) refl ect sampling of subjects already with signifi cant atherosclerotic disease, and therefore, higher PLTPa, which may be a consequence of the underlying pathophysiological processes or a compensatory change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional aspects of the HDL-P not captured by HDL-C measures may explain the recent failures of interventions to raise HDL-C to prevent CVD mortality ( 8,15 ). Of the many functional aspects of HDL, one of the most promising is RCT, whereby lipids are removed from peripheral cells and atherosclerotic plaque by HDL-borne association between PLTPa and acute CVD ( 37,62 ) refl ect sampling of subjects already with signifi cant atherosclerotic disease, and therefore, higher PLTPa, which may be a consequence of the underlying pathophysiological processes or a compensatory change.…”
Section: Discussionmentioning
confidence: 99%
“…The study population is a subset (n = 1,115) of the previously described CLEAR study ( 8,(10)(11)(12)(40)(41)(42)(43)(44)(45)(46)(47) PLTP region SNP associations with PLTPa. SNPs with у 1% frequency identifi ed in the PLTP region between 50 kb upstream of the fi rst codon or downstream of the last (n = 124 SNPs) were included in our analyses of the genetic predictors of PLTPa.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several previous studies have shown that small dense HDL subspecies (i.e., HDL3 subclass), besides their role in reverse cholesterol transport, show additional properties, such as antioxidant, anti-inflammatory, cytoprotective, anticoagulant, and anti-infectious properties, not exhibited by large light HDL (18). This increased value of HDL3 in atheroprotection has been recently supported by several epidemiological studies that have shown an inverse association of HDL3 and not HDL2 with disease progression and clinical event presentation (66,67). Interestingly, both enzymes, LCAT and PON1, have been shown to inhibit LDL oxidation in the absence of HDL and to enhance the antioxidant activity of HDL (68).…”
Section: Discussionmentioning
confidence: 89%
“…33 Evidence from the National Heaert, Lung and Blood Institute Exome Sequencing Project reported a PON1 V109I variant that decreases PON1 arylesterase and increases ischemic stroke risk. 34 In contrast to the PON1 organophosphate activity assays, numerous studies used PON1 single nucleotide polymorphisms that predict organophosphate activity assays as proxies for PON1 function and failed to show mendelian randomization evidence of PON1 with CVD.…”
Section: Genetic Epidemiology: Hdl Particlesmentioning
confidence: 99%